Mission among the Jews - A. van de Beek (Acta Theologica)
The author discusses whether the issue of mission among the Jews deals with the basic question of mission or whether it is the core of the Christian faith. Although both Jews and Christians reject the idea and (more so) mission among the Jews, the author strongly argues for its need, for mission is not the expansion of ideas or cultures, but the telling of the good news of Christ’s death and resurrection. Religion is not based on a doctrine but on an event that must be communicated to all and, first, to the people of God. The first people to do so were Jewish Christians. When Gentile Christians are called to proclaim the gospel to the Jews, they can do so only on the common ground of the Scriptures: the Old Testament. This requires knowledge of the Old Testament that is compatible with the Jewish knowledge of the Scriptures, which must be living letters of Christ as a result of the fullness of the gospel in their lives.